Bound in blood - Mains, Johnny, 1976-; Higson, Charlie, 1958-; Benedict, A. K.; Moore, Alison, 1971-; LaRocca, Eric; Bulkin, Nadia; McKnight Hardy, Lucie; Sharma, Priya; Suttie, Isy, 1978-; Newman, Kim; Rocklyn, Zin E.; Slatter, Angela; et al. (Titan books, 2024)
"A terrifying anthology of stories about the darker side of books." --